Kwashiorkor in Upper Middle Class Suburbia in the United States (FS17-02-19). (13th June 2019) - Chawla, Anupama; Francis, Denease; Daniel, Sherin; Tobin, Michelle
Abstract: Objectives: Malnutrition continues to be a major cause of death worldwide among children aged 5 years and under. We describe two patients who developed kwashiorkor while being predominantly fed rice milk. Methods: An 11-month old Caucasian male presented with a 3-day history of worsening edema, decreased oral intake, diffuse maculopapular rash, and poor weight gain. He was diagnosed with dairy, soy, and sesame allergies by two allergists and was placed on rice milk. Labs revealed hypoalbuminemia, anemia, transaminitis, zinc and copper deficiency. He was started on Elecare Jr and vitamin supplementation with clinical improvement. A 2-year-old Caucasian male presented with a 7-day history of abdominal distension, abdominal pain, edema, and rash. He had multiple food allergies. His diet consisted of diluted almond and rice milk, chips, apples, and corn. He had hypoalbuminemia and anemia with multiple vitamin deficiencies. Results: Kwashiorkor is characterized by severe malnutrition, hypoalbuminemia, edema, irritability, and rash. It is rare in the US but is being reported in patients receiving rice milk as their major source of nutrition. Previously described cases were due to dietary manipulations by the parents. Both our patients were under the guidance of physicians. Rice milk has been suggested as an alternative for patients with milk protein allergy however; not all products on the market have the same nutritional value, with significantly varied fortification. A recent study examined patients diagnosed with CMPA fed an extensively hydrolyzed rice protein-based formula called Novarice. This formula contains 21.9 calories and 0.6 grams of protein per ounce. Both our patients were ingesting Rice Dream which contains only 15 calories and 0.13 g of protein per ounce. Conclusions: Infants who ingest rice milk are at high risk of developing severe malnutrition with hypoalbuminemia, edema, and nutritional deficiencies. It is important to educate not only consumers but health care providers on nutritional composition of these products. Translating an evidence-based study on the benefits of fortified rice milk into clinical practice needs to be performed cautiously since not all rice milk products are nutritionally alike. Funding Sources: None. Supporting Tables, Images and/or GraphsTable 1: